2020
DOI: 10.1177/0309524x20933948
|View full text |Cite
|
Sign up to set email alerts
|

Study of ice accretion on wind turbine blade profiles using thermal infrared imaging

Abstract: Atmospheric icing has been recognized as hindrance in proper utilization of good wind resources in cold regions. There is a growing need to better understand the ice accretion physics along wind turbine blades to improve its performance and for optimal design of anti/de-icing system. This article describes a study of ice accretion along wind turbine blade profiles using thermal infrared imaging. Surface temperature distribution along four different blade profile surfaces is studied at different operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The results showed that the method can detect icing events with high resolution, high precision and high discrimination, accurately measure and identify the icing with a thickness of 0.1 mm, and give a timely warning in the early stage of icing. There are some studies that have used capacitive and resistance sensing technology to measure icing thickness [77,78]. The icing thickness is measured based on changes in capacitance and resistance due to icing accumulation between two charged cylindrical probes or parallel plate capacitors.…”
Section: Icing Monitoring and Safety Status Assessmentmentioning
confidence: 99%
“…The results showed that the method can detect icing events with high resolution, high precision and high discrimination, accurately measure and identify the icing with a thickness of 0.1 mm, and give a timely warning in the early stage of icing. There are some studies that have used capacitive and resistance sensing technology to measure icing thickness [77,78]. The icing thickness is measured based on changes in capacitance and resistance due to icing accumulation between two charged cylindrical probes or parallel plate capacitors.…”
Section: Icing Monitoring and Safety Status Assessmentmentioning
confidence: 99%
“…They also simulated the effect of surface dust accumulation on IRT measurements. Yousuf et al (Yousuf et al, 2021) studied ice accretion on wind turbine blades using FLIR® A615 thermal infrared camera to analyze the effect of liquid water content, angle of attack, temperature and blades profile geometry on ice formation.…”
Section: Infrared Ice-detectionmentioning
confidence: 99%
“…Researchers are currently working on the recognition of ice accretion by infrared thermal imaging, which extracts the shape of ice accretion based on temperature differences between ice and substrate [16][17][18][19][20]. However, a challenge remains the exploration of the relationship between temperature and ice thickness using infrared thermal images, which has made some progress in marine research.…”
Section: Introductionmentioning
confidence: 99%